Antimicrobial activity of Aegle marmelos against clinical pathogens - B. Karthikeyan, K. Suresh, P.K. Senthilkumar, (Journal of Phytology, 2009)
Aegle marmelos is a medicinal herb belongs to the family Rutaceae. The different parts of plants like leaves and flowers are extracted by using the solvent methanol. The methanol extracts were screened for the antimicrobial activity. They showed greater inhibitory effect against both gram positive and gram negative organisms. The organisms used were such as Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis, Salmonella typhi, Staphylococcus aureus. Based on the present investigation results it is concluded that the methanolic extracts of Aegle marmelos has great potential as antimicrobial agent against different microorganisms and they can be used in the treatment of infections diseases caused by the resistant microorganisms.